Study of Immunological Parameters, Hematologic Outcomes And Epidemiology Features of Renal Dysfunction Frequently in Karbala Province, Iraq (Indian Journal of Forensic Medicine & Toxicology, 2020)
Renal failure or dysfunction: A disease occurs by a severe weakness in one kidney or both, they lose abilityto do their functions effectively, resulting in the body’s inability to remove waste and fluids, Leading to asignificant changes in chemistry of blood and body fluid.The study occurred in Karbala province where study samples were collected, which included (124). Samplesdivided in (64) patients and (60) control, patients had another division according to sex (44) male and (20)female. Immunologic parameters include (kidney injury molecules (KIM-1), pro-inflammatory TNF-?, IgGantibodies) Elabscience Kit, concentration in serum was massacred by (ELISA) Technique and hematologictest measured automatically by (Humlate plus-1 Device).The results showed increase in kidney injury in age groups beyond the age of 40 years. A significantly higherincidence of disease among males more than females. Results show significant statically variations in serumlevels:1- kidney injury molecules (KIM-1) levels was increased in serum in patients significantly compare withcontrol.2- (TNF-?) levels was increased in patients than control.3- IgG levels decreased in patients than control.Another routine tests occurs to patients to know the effects of disease on blood variations, the test wasincluded CBC count the results show CBC tests: (WBC, MHC, MCHC, RDWS, RDWC, PLT, PCT, PDWS,PDWC, P-LCC and P-LCR) have no significant differentials while CBC tests: (LYM., MON., GRA., RBC.,HGB., HCT., MCV, MPV) which decrease in patient compare with control significantly.Increase kidney injury and inflammatory in serum patients with disease, by measured some parameters levelsin sera as indicators for disease progression and decrease in some antibodies such as IgG concentration of insera, as well as the hematologic tests referrer to disease may associated with anemia.